Mass transfer effects on mucus fluid in the presence of chemical reaction - Padmavathi Thiyagarajan; Sethamilselvi Sathiamoorthy; Hemalatha Balasundaram; Oluwole Daniel Makinde; U. Fernandez-Gamiz; Samad Noeiaghdam; Shyam Sundar Santra; Mohamed Altanji (Alexandria Engineering Journal, 2023)
The mucus fluid vehicle is impacted by the synthetic response that changes the physical science of liquid due to the thickness of the bodily fluid. Additionally, various issues in the respiratory system might happen because of bodily fluid adequacy. A central point of transportation of immunizations to forestall COVID-19 is the concentration level expected during movement, stockpiling, and dispersion. The current review stated that mucus fluid transportation is restrained through magnetic force originating due to heat variation. Permeable channel over respiratory disease and chemicals due to mass reaction–diffusion variation. The bodily fluid development is surveyed by the force, energy, and diffusion condition influence of body powers because of attractive field, source of heat cause of thermal conduction, resistance due to disease chemical reaction cause of concentration profile. The nonlinear arrangement of incomplete differential conditions is addressed by the Laplace transform technique, and MATLAB programming outcomes are initiated for momentum, temperature, and diffusion fields and inferred that the bodily fluid stream decelerates due to magnetic force. The skin friction, Nusselt number, Sherwood number, and the microorganism’s thickness are assessed and explained exhaustively. Furthermore, microorganisms are occupied in different elements to survey the mucus fluid mechanism.